Association of killer immunoglobulin-like receptor genotypes and haplotypes with acute lymphoblastic leukemia risk - Jameel Al-Tamimi; Suliman Alomar; Ali Aljuaimlani; Lamjed Mansour (Innate Immunity)
Background Killer immunoglobulin-like receptors (KIRs) are key molecules used by natural killer (NK) cells to interact with target cells. These receptors exhibit extensive genotypic polymorphism which has been associated with varying outcomes in immune responses against diseases. This study aimed to investigate the relationships between KIR genotypes and haplotypes with acute lymphoblastic leukemia (ALL) in Saudi patients. Methods A total of 259 Saudi subjects including 145 cases of acute lymphoblastic leukemia (ALL) and 114 healthy controls living in Riyadh were genotyped for 16 KIR genes and the two HLA-C1 and -C2 allotypes using PCR-SSP genotyping method. Results A significant high frequency of the two inhibitory KIR genes; 2DL1 (OR = 2.4; p  < 0.0001) and 3DL1 (OR = 10.87; p  = 0.0068) in ALL compared to healthy group was observed. In contrast, the activating 2DS4 gene was significantly higher in healthy controls (OR = 0.15, p  < 0.0001) compared to ALL patients. Haplotype analysis shows that BX haplogroup was strongly associated with the occurrence of ALL (OR = 4.39; p  < 0.0001). Further combinatory analysis of KIR genes with their HLA-C1 and -C2 ligands demonstrated strong statistically protective effect of the 2DS1-C2 combination from ALL (OR = 0.06; p  = 0.0003). Conclusion This study presents strong evidence supporting the connection between certain KIR genotypes, haplotypes, and KIR-HLA combinations with acute ALL in the Saudi population. The heightened occurrence of inhibitory KIR genes ( 2DL1 and 3DL1 ) and the BX haplotype in ALL patients indicates a possible involvement of these genetic variability with the dysfunctional of NK cells in the context of ALL disease.